Searching for pattern in Lamentations - Salters, R. B. (Old Testament essays, 1998)
In this article some recent attempts to find pattern in the book of Lamentations are examined and found to be deficient. It is then argued that the way forward in this debate is to take as a starting point, the similarity of the chapters of Lamentations to the laments in the book of Psalms, and to take cognizance of the descriptionptions of the bok in the early period of the interpretation of Scripture.